Early Warning System Financial Crisis: Economic Factors and Political Factors - Rachel Bunga Adjani, Catherine; Herlina Sitorus, Nurbetty (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the right indicators in making a financial crisis early warning system by combining economic and political factors. This research is descriptive research with a quantitative approach. The data used are secondary data collected through the official website of the institution and data publications, with variables Financial Crisis, GDP, inflation, interest rates, and political stability. The scope of this study is annual data from Indonesia, South Korea, Malaysia, the Philippines, and Thailand from 1996 to 2022. The data was analyzed through the logit method, with dependent variables 0 and 1. The results showed that the variables inflation, GDP, and domestic credit had a significant effect on the occurrence of the financial crisis.